The more the merrier? On the optimality of market size restrictions - Colin von Negenborn (Review of Economic Design, 2022)
This paper provides a novel rationale for the regulation of market size when heterogeneous firms compete. A regulator seeks to maximize total welfare by choosing the number of firms allowed to enter the market, e.g. by issuing a certain number of licenses. Opening up the market for more firms has a two-fold effect: it increases competition and thus welfare, but at the same time, it also attracts more cost-intensive firms, driving down average production efficiency. The regulator hence faces a trade-off between raising beneficial competition and detrimental costs. If goods are sufficiently substitutable, the latter effect can outweigh the former. It is then optimal to restrict the market size, rationalizing a limit to competition. This possibility result holds even in the absence of entry costs, search costs or increasing returns to scale, which previous literature required.
Keywords: D43; L13; L51; 330; Regulation; Imperfect competition; Oligopolies